Pengaruh Set Kesempatan Investasi Terhadap Hubungan Antara Kepemilikan Manajerial dan Aliran Kas Bebas dengan Tingkat Leverage Perusahaan - Raino Wirjono, Endang (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2009)
Agency Ã‚Â theory Ã‚Â mentions Ã‚Â that Ã‚Â leverage Ã‚Â (debt) Ã‚Â is Ã‚Â one Ã‚Â of Ã‚Â mechanism Ã‚Â used Ã‚Â by shareholders Ã‚Â toÃ‚Â minimize agency problem with manager. In this context, previous researchers show that leverageÃ‚Â was influenced by free cash flow and insider ownership (managerial ownership). This researchÃ‚Â aims Ã‚Â to Ã‚Â examine Ã‚Â the determinants Ã‚Â of Ã‚Â leverage Ã‚Â in Ã‚Â a Ã‚Â research Ã‚Â model Ã‚Â and Ã‚Â treats investmentÃ‚Â opportunity Ã‚Â set Ã‚Â (IOS) Ã‚Â as Ã‚Â moderating Ã‚Â variable Ã‚Â that Ã‚Â will Ã‚Â influence the Ã‚Â relationship Ã‚Â between Ã‚Â freeÃ‚Â cash flow and managerial ownership with leverage. By using sample consist of 38 manufacturingÃ‚Â companies, result from moderated Regression Analysis (MRA) statistically shows evidence thatÃ‚Â IOS Ã‚Â influences Ã‚Â the relationship Ã‚Â between Ã‚Â free Ã‚Â cash Ã‚Â flow Ã‚Â and Ã‚Â leverage. Ã‚Â This Ã‚Â result supportedÃ‚Â TarjoÃ¢â‚¬â„¢s research (2002).